Degradation of glass fiber reinforced polymer (GFRP) material exposed to tropical atmospheric condition - Mousay, Mohammed; Chai, Yew Ying; Doh, Shu Ing; Lim, Kar Sing (Trans Tech Publications, Switzerland, 2021)
Fibre reinforced polymers (FRPs) have emerged as popular materials for structural application in recent decades due to numerous of advantages. Despite the growing body of research on the use of glass fibre reinforced polymers (GFRP) composites in repairing and retrofitting the important structures such as oil and gas pipelines, the lack of comprehensive data on the long-term degradation mechanism for these materials is still impeding their widespread use in open-air structures repairs particularly in tropical climate locations such as Malaysia. Therefore, this paper presents an experimental investigation to determine the influence of tropical atmospheric condition on tensile properties of the GFRP. In this study, a set of GFRP samples were fabricated using epoxy resin as polymer matrix and woven E-glass fibres as reinforcing materials. These samples were exposed to tropical atmospheric condition in Malaysia for a period of four months. Tensile test was carried out for each sample before and after four-months period of exposure. The experimental tensile test results recorded a 15% reduction in tensile strength after 4 months of exposure as compared to its original strength. Further, the dominant failure mode of the exposed sample was characterized with longitudinal splitting of the fibres without completely breaking out. Overall, the tropical atmospheric condition has a noticeable impact on the GFRPs tensile strength degradations over the exposure duration.